Effects of high-crime environments on educational efficiency, a spacial case (2021)
Education plays a vital role in our societies, well it gives individual and societal benefits. Nevertheless, urban crime affects educational performance and achievement (Ferguson & Michaelsen, 2013) and other possible consequences. Moreover, if crime impacts the quality and quantity of education, the returns from this process also decrease. The literature reviewed suggests that this study is one of the first that study this relationship. Hence, we aim to identify and estimate the impact of crime environments on the educational efficiency in Cali and the construction of the real environment surrounding the schools. To achieve it, we use a non-parameter conditional order-m to estimate the relative efficiency of each school throughout the city. We discover four main findings. First, it is crucial of considering issues related to urban crime on educational efficiency for policymakers. Second, it is clear there is a negative effect of homicides on educational efficiency; the schools lose efficiency operating in these environments. Third, the relationship between crime and net educational efficiency loss is not linear; it has an inverted-U shape. Finally, since a certain level of homicides, the schools can start to be tolerant in front of increasing crime levels without necessarily repercussions in their efficiency.